Impact of agricultural land use rights transfer on carbon emission intensity of cultivated land--Empirical evidence based on panel data of 30 provinces in China. - Yuetang Chen; Haofan Zhang (PLoS ONE)
In the context of high-quality agricultural development, farmers increasingly engage in agricultural land use rights transfer(ALURT) to achieve large-scale operations and improve agricultural production efficiency. However, large-scale agricultural operations often lead to mechanized production, which may cause higher carbon emissions, contradicting the principles of green agricultural development. This study aimed to assess the actual impact of ALURT on the carbon emission intensity (CEI) of croplands and explore the role of agricultural large-scale operations in this relationship. To achieve this, the CEI of arable land across 30 provinces in China from 2014 to 2022 was measured, and the impact of ALURT on the CEI was analyzed using a two-way fixed-effects model, a mediated-effects model, and a threshold-effects model. These findings suggested that the total carbon emissions and CEI of arable land in China have declined annually since 2015. Southeastern coastal provinces, including Shanghai and Zhejiang, have the highest CEI of croplands. ALURT significantly reduced the CEI for arable land. Moreover, mechanism testing revealed that large-scale operations did not have a mediating effect but instead exhibited a threshold effect. When the scale of agricultural operations grew to the threshold, the inhibition of ALURT on CEI could be amplified.